From Catastrophe to Crisis: Francesca Antonini’s Caesarism and Bonapartism in Gramsci - Dainotto, Roberto (International Gramsci Journal, 2023)
This is the abstract of a review by Roberto Dainotto of the book by Francesca Antonini, Caesarism and Bonapartism in Gramsci. Hegemony and the Crisis of Modernity (Leiden and Boston, Brill 2020).